SOSIOLOGI MODERASI BERAGAMA DALAM TRADISI BAHTSUL MASAIL PONDOK PESANTREN AL-FALAH PLOSO: STUDI TENTANG ARGUMENTASI, ADAB IKHTILAF, DAN KULTUR MUSYAWARAH - Zaidatu Ulfa (Universitas Islam Negeri Sumatera Utara Medan, 2026)
The tradition of bahtsul masail in pesantren is not only a forum for discussing Islamic law, but also a space where students learn to respect differences and build a culture of deliberation. This research examines how the bahtsul masail tradition at Al-Falah Ploso Islamic Boarding School reflects the practice of religious moderation in everyday learning activities. The study focuses on the way students deliver arguments based on classical Islamic texts, respond to differing opinions, and understand social issues through discussion forums. This research used a qualitative ethnographic approach through observation, interviews, and documentation. The findings show that bahtsul masail encourages students to develop critical thinking, respect different perspectives, and maintain ethical discussion practices. The tradition also helps students connect religious understanding with contemporary social realities. This study is expected to contribute to discussions on Islamic education and pesantren intellectual traditions.